Tasawuf Inklusif Tarekat Shafa’i - Saifuddin, Saifuddin (Proceedings of Annual Conference for Muslim Scholars, 2025)
Sufism, as the inner dimension of Islam, offers a spiritual path to universal peace and compassion. The Tarekat Shafa'i emphasizes the approach of love (mahabbah), simplicity (zuhd), and openness to socio-cultural diversity. This study uses a qualitative phenomenological method, with the aim to understanding the meaning of spiritual experience in depth. The research subjects consisted of mursyid thariqoh, caliphs, abdals, and active practitioners of the Tarekat Shafa'i in Sidoarjo, selected through purposive sampling. Data collection techniques included: in-depth interviews, participant observation, and documentation. Data analysis was carried out using phenomenological analysis (epoché-reduction–textural/structural description) in accordance with Husserl's phenomenological method. Inclusive Sufism in the Tarekat Shafa'i is a manifestation of Islamic spirituality that integrates universal Islamic values ​​with local wisdom. Through an approach of love, tolerance, and balance, this order has built a peaceful and contextual model of religiosity